Inovasi Joint Bambu Pada Tenda Tradisional Bali (Taring) Dengan Material Besi - I Putu Ananta Ari Pramana; I Gede Krisna Adi Pratama; I Gusti Agung Prianka Lakshmi; Anak Agung Gede Raka Gunawarman; I Wayan Wirya Sastrawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
Taring is a building that is often used as a shade during the Yadnya ceremony, in the workmanship of traditional Balinese taring the material used is bamboo with a fairly complicated manufacturing process and requires a long time span. Complicated work and a long time create a combination of materials used in the connection system, the material used is iron material. The combination of these connections occurs because on the basis of industrial needs with reasons for work efficiency. Tetaring with a combination of materials contained in the connection is targeted at weddings, ceremonial events, and others, for religious events it is not recommended to use this fang innovation, because the grip and meaning of traditional Balinese teeth are very influential in launching the course of religious ceremonies. This research will use a quantitative method approach by conducting experiments, collecting data and supporting journals to obtain information that will be used for consideration. The experimental method will be carried out directly by trying the product made, data collection in this study is by observing, documenting data in the form of photos, and other articles from journals and the internet.